Description of Dociostaurus biskrensis sp. nov. and male allotypes of four species: Pamphagulus bodenheimeri dumonti, P. uvarovi, Sphingonotus ebneri and Notopleura pygmaea (Orthoptera: Acridoidea) in the region of Biskra, Algeria - Moussi, Abdelhamid; Abba, Abderrahmane; Harrat, Abboud; Petit, Daniel (Zootaxa, 2014)
The new species Dociostaurus biskrensis Moussi & Petit 2013 was collected in the region of Biskra, at the arido-Saharan limit of Eastern Algerian. We also describe the males of four species for which only females were known: Pamphagulus bodenheimeri dumonti, P. uvarovi, Notopleura pygmaea and Sphingonotus ebneri. The key to the genus Dociostaurus in North Africa is given. The species P. uvarovi and Notopleura pygmaea are new for the Algeria. The diets and life cycles of D. biskrensis and of the two species of Pamphagulus are defined.